2016
DOI: 10.1159/000446954
|View full text |Cite
|
Sign up to set email alerts
|

Primary Retroperitoneal Cystoadenocarcinoma: A Systematic Review

Abstract: Background/Aims: The aim of this study was to perform a systematic review on primary retroperitoneal cystoadenocarcinoma (PRC), which is an extremely rare disease. Methods: According to PRISMA guidelines, all the literature about PRC from 1977 to 2015 was reviewed. Thirty articles were selected; characteristics of the patients were collected and described; time to recurrence and overall survival (OS) were investigated when available. Results: Thirty seven patients were included of whom 33 were females; the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
2
0
4
Order By: Relevance
“…One systematic review and one meta-analysis of PRMCa, and one meta-analysis of PRMN have presented general information on epidemiology and clinical features; the results of these prior studies are consistent with our study. 2 , 3 , 21 In previous studies, serum tumour markers such as CEA, CA 125, and CA 199 were reportedly elevated in a small portion of patients, but it has been demonstrated that they have neither diagnostic nor prognostic significance, as is the case with pre-operative biopsy. 2 , 3 In our series, not surprisingly, these aforementioned diagnostic tools exhibited poor diagnostic efficacies.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review and one meta-analysis of PRMCa, and one meta-analysis of PRMN have presented general information on epidemiology and clinical features; the results of these prior studies are consistent with our study. 2 , 3 , 21 In previous studies, serum tumour markers such as CEA, CA 125, and CA 199 were reportedly elevated in a small portion of patients, but it has been demonstrated that they have neither diagnostic nor prognostic significance, as is the case with pre-operative biopsy. 2 , 3 In our series, not surprisingly, these aforementioned diagnostic tools exhibited poor diagnostic efficacies.…”
Section: Discussionmentioning
confidence: 99%
“…20 Our finding, however, is also consistent with the results from 2 recent metaanalyses on PRMT-Cs. 3,21 Because symptoms are mostly nonspecific they do not contribute to a correct diagnosis. The presence of symptoms did not differentiate benign and malignant disease.…”
Section: Diagnosismentioning
confidence: 99%
“…Conform unei revizuiri sistemice a literaturii de către B.Pellegrino și coaut. [38] a constatat că 46% din observațiile CACMR provin din țările asiatice.…”
unclassified
“…Principiul de bază al tratamentului chirurgical este îndepărtarea completă a tumorii fără a-i încălca integritatea, în principal prin abord laparotomic [37,38,39,40,41,42,43,44,49]. Cu toate acestea, rupturi tumorale intraoperatorii au fost observate în 13% din cazuri [38].…”
unclassified
See 1 more Smart Citation